Perancangan dan Penyusunan Sistem Persediaan Berbasis Microsoft Access pada PT. Xinhe Plastic Silicone - Anita Anita; Jeny Jeny (Universitas Internasional Batam, 2021)
PT. Xinhe Plastic Silicone is a company that is growing rapidly in Batam City which is engaged in the industrial sector that produces various types of silicone which currently has the aim of having an efficient supply system compared to now. Inventory in a company is something important. Based on the results of research that has been done in the company, the company's inventory system has been changed from an excel system to an access system that produces useful data for every user of that information. In this study, it is hoped that business owners will continue to use the inventory recording system with Microsoft Office Access in order to be able to make inventory reports accurately and precisely.